Influence of accompanying ions on the efficiency of the water defluorination process by a modified ceramic membrane - Dulneva, T.Yu.; Deremeshko, L.A.; Baranov, О.І.; Goncharuk, V.V. (Reports of the National Academy of Sciences of Ukraine, 2022)
Were investigated the regularities of the process of defluorination of solutions using a tubular microfiltration ceramic membrane made of clay minerals, developed by the A. V. Dumansky Institute of Colloid and Water Chemistry of NAS of Ukraine. Natural water, as a rule, contains together with fluorides other macrocomponents (accompanying ions) which can influence parameters of process of its defluorination. Therefore, the effect of various ions, in particular, Cl–, HCO –3 and SO–24, on the fluoride retention capacity of the ceramic membrane modified with Al(III) hydroxy compounds was studied. It is shown that with increasing concentration of salts containing these ions, when adding them to the initial solutions separately, the concentration of F– in the permeate increased. It was found that SO–24 ions had the greatest negative effect on the defluorination process. The presence of each of these ions separately provided the MAC F– in drinking water and the the mixture of these ions significantly reduced the efficiency of the process. The normative value MAC of fluorine in drinking water was reached only at k < 40 %, which is not enough for practical use. Given the negative effect of typical natural anions on the characteristics of the process of defluorination of the solution by a modified ceramic membrane, it was necessary to determine the conditions under which the MAC of F– ions in drinking water can be achieved. It was found that the efficiency of the solution defluorination process can be increased by increasing the concentration of Al(III) in the membrane-supporting additive. Since the concentration of fluorides in many water sources of Ukraine reaches 2. 5—5. 0 mg/dm3, to achieve their normative values of MАC in drinking water, it is acceptable to use a concentration of 15 mg/dm3 Al(III) in a membrane- supporting additive for purifying waters from fluorides using a modified ceramic membrane in the presence of other anions in the water.